Effect of substituting bacitracin with garlic, blueberry or turmeric in the diet on growth performance, carcass traits, lipid content and meat antioxidant status of turkeys - Paredes, Manuel (2021)
The aim of this study was to determine the effect of adding garlic, cranberry or turmeric as a replacement for bacitracin in turkey diets on growth performance, carcass characteristics, lipid content and antioxidant status of meat. In total, 500 male Hybrid Converter turkeys were used from 42 to 98 days of age. The birds were assigned to five dietary treatments (5 repetitions per treatment and 10 birds for repetition) and fed isocaloric and isonitrogenated diets. In the control group no additive ingredients were added, while the experimental groups consumed diets with 0.05% zinc bacitracin, 1% garlic powder, 1% cranberry powder or 1% turmeric powder. The additives had no effect on growth performance and carcass yield, while turkeys fed diets containing garlic, blueberry, and turmeric showed lower abdominal fat weight, lower cholesterol content, and lower lipid oxidation of meat in comparison to meat from turkeys that consumed the control or the bacitracin diet.